2002
DOI: 10.1038/sj.ijo.0801987
|View full text |Cite
|
Sign up to set email alerts
|

The hormonal responses of lipoprotein lipase activity and lipolysis in adipose tissue differ depending on the stage of the estrous cycle in female rats

Abstract: OBJECTIVE: This study was designed to elucidate whether there were differences in the hormonal responses of the parameters involving triacylglycerol (TG) deposition and mobilization in adipose tissue among the stages of the estrous cycle in female rats. MEASUREMENTS: Adipose tissue was obtained from the parametrial region in female rats at each stage of the estrous cycle. Lipoprotein lipase (LPL) activity in the extracts of acetone=ether powders of the tissues was measured as a parameter for TG deposition. Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…FAS has been known as one of the lipogenic enzymes which facilitate the synthesis and cytoplasmic storage of massive amounts of triglyceride [20]. LPL acts as catalyst in hydrolysis reactions of triglyceride, in which plasma triglyceride is metabolized to free fatty acids for triglyceride synthesis with adipose cells [21]. Leptin is exclusively secreted in proportion to their triglyceride stores in adipocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…FAS has been known as one of the lipogenic enzymes which facilitate the synthesis and cytoplasmic storage of massive amounts of triglyceride [20]. LPL acts as catalyst in hydrolysis reactions of triglyceride, in which plasma triglyceride is metabolized to free fatty acids for triglyceride synthesis with adipose cells [21]. Leptin is exclusively secreted in proportion to their triglyceride stores in adipocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those reported in several other studies 22,23) . Fat accumulation and weight gain in OVX may be attributable to improper functioning of the inhibition of fat synthesis, due to the effects on hormone metabolism caused by decreased oestrogen secretion in OVX rats 24) . In this study, large amounts of subcutaneous fat were observed when the abdomens of Group 3 rats were opened under general anaesthesia at 24 weeks after surgery, and this thick subcutaneous fat is thought to be a factor contributing to the increased weight.…”
Section: Changes In Body Weightmentioning
confidence: 99%
“…Estrogen increases hormone-sensitive lipase, which is the rate-limiting enzyme in lipolysis (Palin et al 2003). Estrogen decreases lipoprotein lipase (LPL) enzyme activity in humans and animals, which is expected to lead ultimately to a decrease in TG deposition in fat cells (Homma et al 2000, Yamaguchi et al 2002. Estrogen also represses the activity of hepatic lipase, an enzyme that hydrolyzes TG and phospholipids in lipoproteins, resulting in an increase in high-density lipoprotein (HDL) cholesterol (Jones et al 2002).…”
Section: Introductionmentioning
confidence: 99%